Software Technologies for Embedded and Ubiquitous Systems 8th IFIP WG 10.2 International Workshop, SEUS 2010, Waidhofen/Ybbs, Austria, October 13-15, 2010. Proceedings - Min, Sang Lyul.; Pettit, Robert; Puschner, Peter; Ungerer, Theo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 8th IFIP WG 10.2 International Workshop on Software Technologies for Embedded and Ubiquitous Systems, SEUS 2010, held in Waidhofen/Ybbs, Austria, in October 2010. The 21 revised full papers presented together with the abstracts of two invited talks were carefully reviewed and selected from 30 submissions. The papers are organized in topical sections on hardware, real-time systems, model-based design and model-checking, sensor nets, error detection and system failures, hard real-time, middleware and smart spaces, and function composition and task mapping.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Information Systems; Computer Science; Software Engineering; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl.Internet).; Programming Techniques; Management of Computing and Information Systems